The Role of Islamic Principles in Change Management Success: An ADKAR-Based Evaluation at AKN Putra Sang Fajar Blitar - Utama, Adiguna Sasama Wahyu; Muluk, Muchamad Saiful (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This study investigates the relationship between the application of Islamic principles and the successful implementation of the ADKAR change management model at AOKI Putra Sang Palat Bilau. The main objective was to determine if Islamic values significantly influence the perceived success of each ADKAR element: Awareness, Desire, Knowledge, Ability, and Reinforcement. The research employed a quantitative method, using survey data from 28 respondents. The data was analyzed using descriptive statistics and inferential techniques, including correlation and linear regression. The results show a very strong positive correlation (r = 0.986), indicating that Islamic principles explain 97.1% of the variance in overall ADKAR success. Among the ADKAR elements, 'Desire' had the highest attainment level. Statistically significant relationships were found between Islamic principles and all ADKAR elements, with the strongest impact on 'Ability'. The regression analysis confirmed that Islamic principles are a powerful predictor for ADKAR scores. In conclusion, the research objectives were achieved, demonstrating that integrating Islamic principles significantly enhances change management initiatives. This provides a valuable framework for organizations in similar cultural contexts to foster successful and sustainable change.